Essentials of general mathematics - Helma Y. Mesa (Makati City : Diwa Learning Systems Inc., 2023)
"This textbook is designed to equip you with algebraic, business and logical skills along with the essential 21st century skills needed in facing the world today. Opportunities for you to learn by experience, work independently or collaboratively and reflect on your understanding are integrated in the activities in the modules."
Includes notes and bibliography.
English text.